2020
DOI: 10.3389/fgene.2020.571219
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of SNP Array Analysis in Prenatal Diagnosis: A Cohort Study of 5000 Pregnancies

Abstract: Background: Single nucleotide polymorphism array (SNP-array) has been introduced for prenatal diagnosis. We aimed to evaluate the clinical value of SNP-array in the diagnosis of fetal chromosomal anomalies. Methods: A retrospective study was conducted on 5000 cases tested by SNP-array, and the results of 4022 cases analyzed by both karyotyping and SNP-array were compared. Results: SNP-array analysis of 5000 samples revealed that the overall abnormality detection rate by SNP-array was 12.3%, and the overall det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…Previous studies [ 8 , 11 , 29 , 30 ] have demonstrated the clinical utility of CMA and WES in prenatal diagnosis, and a combination of these two approaches for each case has been warranted. In this prospective study, we applied WGS in parallel with CMA plus WES to 111 fetuses with a broad range of structural or growth anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 8 , 11 , 29 , 30 ] have demonstrated the clinical utility of CMA and WES in prenatal diagnosis, and a combination of these two approaches for each case has been warranted. In this prospective study, we applied WGS in parallel with CMA plus WES to 111 fetuses with a broad range of structural or growth anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the NIPT had weak efficacy for CNV detection, which may be associated with the refusal from some samples to undergo further CMA validation, as well as the interference of low fetal free DNA levels, fetal placenta chimerism, and maternal-derived chromosome copy number abnormalities [ 30 , 31 ]. Therefore, when the fetus is detected with CNV by NIPT, the medical history of the pregnant woman shall be further understood, and the need for interventional prenatal diagnosis shall be considered together with the results of prenatal ultrasound, and the detection rate of abnormal chromosomes shall be further improved by combining chromosome karyotyping and CMA detection techniques [ 32 , 33 ]. Fetal parental chromosomes shall be selected for control analysis when necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, cases of SMS and PTLS are detected using chromosomal microarray analysis (CMA). CMA is divided into two categories (Brady and Vermeesch, 2012), array-based comparative genomic hybridization (array-CGH) and single-nucleotide polymorphism arrays (SNP-array) (Xiang et al, 2020). SNParray can not only detect the CNV, but it can also detect abnormalities such as uniparental disomy, low level chimera, and triploidy (Zhang Y. et al, 2020).…”
Section: Discussionmentioning
confidence: 99%